Graphene as an active virtually massless top electrode for RF solidly mounted bulk acoustic wave (SMR-BAW) resonators. (1st February 2018) - Knapp, Marius; Hoffmann, René; Lebedev, Vadim; Cimalla, Volker; Ambacher, Oliver
Abstract: Mechanical and electrical losses induced by an electrode material greatly influence the performance of bulk acoustic wave (BAW) resonators. Graphene as a conducting and virtually massless 2D material is a suitable candidate as an alternative electrode material for BAW resonators which reduces electrode induced mechanical losses. In this publication we show that graphene acts as an active top electrode for solidly mounted BAW resonators (BAW-SMR) at 2.1 GHz resonance frequency. Due to a strong decrease of mass loading and its remarkable electronic properties, graphene demonstrates its ability as an ultrathin conductive layer. In our experiments we used an optimized graphene wet transfer on aluminum nitride-based solidly mounted resonator devices. We achieved more than a triplication of the resonator's quality factor Q and a resonance frequency close to an 'unloaded' resonator without metallization. Our results reveal the direct influence of both, the graphene quality and the graphene contacting via metal structures, on the performance characteristic of a BAW resonator. These findings clearly show the potential of graphene in minimizing mechanical losses due to its virtually massless character. Moreover, they highlight the advantages of graphene and other 2D conductive materials for alternative electrodes in electroacoustic resonators for radio frequency applications.